Experimental investigation on performance of homogeneous charge compression ignition engine fueled with palm oil based biodiesel - Muhamad Tobib, Hasyuzariza (2019)
Fossil fuel is the main resource to fuel Internal Combustion Engine (ICE). High gases exhaust emission and finite resources of fossil fuel are the major problems in ICE industry. Biodiesel fuels with Homogeneous Charge Compression Ignition Engine (HCCI) have the potential to replace the current conventional engine, which can reduce the emissions levels and also the dependency towards fossil fuel. The objectives of the study are to improve the performance and emissions levels of HCCI engine fuelled with palm oil-based biodiesel. For this purpose, single cylinder diesel engine with a port fuel injector and heated intake air was used to operate the HCCI engine at 2700 rpm. The fuels used for this study were diesel and palm oil-based biodiesel with four different blends of 5%, 10%, 15%, and 20% (POB5, POB10, POB15, and POB20, respectively). The parameters varied for the study were different air fuel ratio (lambdas,λ) of 3.1, 2.9, 2.6, 2.4 and intake air temperature of 70, 80, and 90°C. When using diesel fuel on HCCI mode, engine power, torque, brake thermal efficiency (BTE) were lower and brake specific fuel consumption (BSFC) was higher compared to compression ignition direct injection (CIDI) mode. The in-cylinder pressure pattern and heat release rate (HRR) for HCCI mode shows the combustion is advanced and the peak is higher at rich mixture compared to CIDI mode. The power and torque produce from HCCI mode is lower compared to CIDI mode by 12%. On both engine mode, the power produce for POB is reduced by 6% than diesel fuel. The BSFC for HCCI was higher than CIDI mode, however, BSFC reduced by 13% as increased POB. The BTE in HCCI reduced by 5% than the CIDI mode. The BMEP reduced when operated in HCCI mode by 13% whereas, increase by 7% when increased air intake temperature. Nitrogen dioxide (NOx) emission of HCCI reduces drastically while hydrocarbon (HC) and carbon monoxide (CO) are higher than CIDI mode. NOx emissions at HCCI mode reduce by over 90%. By increasing the amount of biodiesel will increase the NOx emissions but NOx at HCCI mode still lower than that of CIDI. When the amount of POB increased HC and CO were improved (decrease) by 15% and 18% respectively. The emission of carbon dioxide (CO2) was also decreased by 25%. This means that biodiesel fuel improved the emission of HCCI. Therefore, it can be concluded that POB was one of potential alternative fuel to replace the conventional diesel fuel in HCCI engine, as it provides the alternative way to reduce the dependency to fossil fuel, thus decreasing the percentage of emission levels.